Pragmatism in Police Stations: An Evaluation of the Violation of Grice’s Maxims in Suspects’ Interrogations - Anjorin-Ojewole, Ruth; Idowu, Olubunmi (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
During police interrogations, accused persons flout or violate conversational maxims to seek a soft landing or escape the law's wrath. Hence, this study evaluates the frequency at which Grice's Maxims were violated during suspects' interrogations. The study identifies these violations based on four maxims: quality, quantity, manner, and relation/relevance results of this study indicate that accused individuals often violate the maxim of quantity to create distractions and divert attention from incriminating evidence during police investigations. The results also show that accused persons violate the maxim of manner by making obscured statements to reduce tension during interrogations. This paper concludes that in suspects' interrogations, accused persons use flouting or violation of Grice's Maxims as communicative tools to escape the punishment(s) apportioned for crime(s) that they commit directly or indirectly.